Vertical Movement of the Spores of Metarhizium Anisopliae (Metsch.) Sorokin through Sand and Soil - Reinke, Marjorie T. (University of Wisconsin-Stevens Point, College of Natural Resources, 1981)
The purpose of this research was to determine whether spores of the green muscardine fungus, Metarhizium anisopliae (Metsch.) Sorokin would migrate through sand and soil by the action of water and a wetting agent under laboratory and field conditions. M. anisopliae is an entomogenous pathogen occurring naturally in soils and is widely used in experimental microbial control attempts. Knowledge of the migration of the spores of M. anisopliae could establish the fungus as an effective agent in controlling hard-to-reach soil inhabiting insect pests and encourage its use in the field as a biological control agent. Laboratory trials consisted of placing a spore suspension of M. anisopliae on the surface of three types of sterile soils, i.e. coarse sand, sand-loam mixture, and soil of the Plainfield series which had been placed in plexiglas columns. This topical application was followed by 150 ml of sterile distilled water. Samples of the soils were taken at 5cm intervals to a depth of 35cm. Spores were found to have traveled to an average depth of 30cm in the sand and Plainfield soil and 20cm in the sand-loam mixture. Unsterile Plainfield soil was placed in a stainless steel column and treated in the same manner as the sterile soils. In this soil, the spores migrated to a depth of 20cm. The surface of eight one-quarter square meter field plots were sprayed with a spore suspension of M. anisopliae. . At the end of two months, the fungus was found at a depth of 18cm. M. anisopliae had migrated to a depth of 30cm after four months. There was no evidence that M. anisopliae occurred naturally in the soils of the test area. A bioassay was devised to determine virulence of the spores after traveling through the soils. The larvae of the greater wax moth (Galleria mellonella) were inoculated with spores of M. anisopliae which were obtained from the cultures of the laboratory and field trials. All the larvae died of green muscardine disease. Based on an evaluation of past research and this investigation, it is believed that M. anisopliae has a high potential as a microbial control agent against soil-inhabiting insects especially in conjunction with a pest management system such as an integrated control program.